2004
DOI: 10.1142/s1088424604000398
|View full text |Cite
|
Sign up to set email alerts
|

Efficient oxidations and photooxidations with molecular oxygen using metal phthalocyanines as catalysts and photocatalysts

Abstract: Metal phthalocyanines can be very efficient as catalysts and photocatalysts in oxidation reactions using molecular oxygen as oxidant. Different types of soluble low molecular weight or oligomeric and insoluble heterogeneous catalysts and photocatalysts were developed. The heterogeneous metal phthalocyanines exist either impregnated on SiO 2, Al 2 O 3, charcoal and TiO 2 or covalently and coordinatively bound on SiO 2 and organic polymers or ionically bound on an organic ion exchanger. The catalytic oxidations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
77
0
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 164 publications
(81 citation statements)
references
References 74 publications
0
77
0
3
Order By: Relevance
“…Their distinct physicochemical properties and the unique redox chemistry of their metal complexes have brought about their incorporation into a large number of donor-acceptor systems in which they function efficiently as light-harvesting substances and electron donors to an acceptor unit [17]. Their metal complexes have also been reportedly used for various photocatalytic and electrocatalytic applications [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their distinct physicochemical properties and the unique redox chemistry of their metal complexes have brought about their incorporation into a large number of donor-acceptor systems in which they function efficiently as light-harvesting substances and electron donors to an acceptor unit [17]. Their metal complexes have also been reportedly used for various photocatalytic and electrocatalytic applications [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…
Abstract:The effects of seven macrocyclic compounds comprising four phthalocyanines (Pcs) namely 1,4,8,11,15,18,22,2,3,9,10,16,17,23,2,9,16, and 29H,31H-phthalocyanine (Pc4), and three naphthalocyanines namely 5,9,14,18,23,27,32,2,11,20, properties of the compounds were also investigated. All the studied compounds showed appreciable inhibition efficiencies, which decrease with increasing temperature from 30 °C to 70 °C.
…”
mentioning
confidence: 99%
“…[25,26] Phthalocyanines were investigated in detail for the photocatalytic oxidations of sulfur compounds, phenols and in organic synthesis. [8,16,25,26] Further, phthalocyanines are active photosensitizers in the photodynamic therapy of cancer. [27] In the case of phthalocyanines as sensitizers thiols are oxidized under irradiation to sulfonic acids (Equation 2).…”
Section: Photocatalytic Activity Of Ionic Phthalocyanines In the Presmentioning
confidence: 99%
“…[27] In the case of phthalocyanines as sensitizers thiols are oxidized under irradiation to sulfonic acids (Equation 2). [16,25] [28,29] Singlet oxygen subsequently oxidizes the thiol to the corrsponding sulfonic acid (Equation 5). It will be shown that the addition of fullerene derivatives can positively influence the photocatalytic activity of phthalocyanines in the photooxidation.…”
Section: Photocatalytic Activity Of Ionic Phthalocyanines In the Presmentioning
confidence: 99%
See 1 more Smart Citation